Long-term improvement by ozone treatment in chronic pain secondary to chemotherapy-induced peripheral neuropathy: A preliminary report - Clavo, Bernardino; Rodríguez-Abreu, Delvys; Galván, Saray; Federico, Mario; Martínez-Sánchez, Gregorio; Ramallo-Fariña, Yolanda; Antonelli, Carla; Benítez, Gretel; Rey-Baltar, Dolores; Jorge, Ignacio J; Rodríguez-Esparragón, Francisco; Serrano-Aguilar, Pedro (Frontiers in Physiology, 2022)
Background: Pain secondary to chemotherapy-induced peripheral neuropathy (CIPN) can limit the administration of chemotherapy, cancer-treatment outcomes, and the quality of life of patients. Oxidative stress and inflammation are some of the key mechanisms involved in CIPN. Successful treatments for CIPN are limited. This report shows our preliminary experience using ozone treatment as a modulator of oxidative stress in chronic pain secondary to CIPN. Methods: Ozone treatment, by rectal insufflation, was administered in seven patients suffering from pain secondary to grade II or III CIPN. Pain was assessed by the visual analog scale (VAS). Results: All patients, except one, showed clinically relevant pain improvement. Median pain score according to the VAS was 7 (range: 5–8) before ozone treatment, 4 (range: 2–6) at the end of ozone treatment (p = 0.004), 5.5 (range: 1.8–6.3) 3 months after the end of ozone treatment (p = 0.008), and 6 (range: 2.6–6.6) 6 months after the end of ozone treatment (p = 0.008). The toxicity grade, according to the Common Terminology Criteria for Adverse Events (CTCAE v.5.0), improved in half of the patients. Conclusion: This report shows that most patients obtained clinically relevant and long-lasting improvement in chronic pain secondary to CIPN after treatment with ozone. These observed effects merit further research and support our ongoing randomized clinical trial (NCT04299893).